The impact of mHealth on adolescent global health outcomes: A scoping review of mHealth initiatives - Patientia, Ramonde Fiona (Department of Human Biology, 2019)
Negative health behaviour during the period of adolescence contributes to the global burden of mortality, chronic disease, and preventable disability from physical injury. It is therefore essential to encourage positive health behaviour such as on-time vaccination, safer sex practices, and early recognition of infectious conditions and mental illness, before complications arise from unprotected sexual debut or undetected illness. Our project aims to determine the favourable aspects of global mHealth interventions as applied to adolescent health outcomes for knowledge transfer to adolescent infectious disease programmes in low and middle-income countries (LMIC’s). mHealth refers to the integration of mobile or wireless technology for health delivery and promotion and may appeal to adolescents as it allows for interactive, personalized, two-way communication on various digital platforms. However, it remains unclear what specific interventions work best to target vulnerable adolescents in LMIC’s, as most of the evidence for mHealth stems from studies in high-income countries, conducted on groups other than adolescents such as caregivers, health workers and adult patients. This report is a scoping review examining the global evidence of mHealth efficacy for common adolescent conditions, in order to gain insight into the types of interventions that best target adolescents for biological and behavioural health outcomes. These insights will facilitate knowledge transfer for the implementation of adolescent mHealth infectious disease management, and identification of research gaps. We included published and unpublished studies between 31 January 1990 and 30 November 2017, with no language limitation. Primary studies included adolescents (defined as 10-19 years of age) of any gender, location, or ethnicity, with access to a mobile phone or wireless device used for a healthrelated outcome. Studies reported on health outcomes of HIV, TB, vaccine-preventable disease, depression, suicide, road traffic accidents and substances other than tobacco use. Purely qualitative study designs and voice-only calls were excluded. Despite the potential appeal of mHealth among adolescents, there is unclear overall evidence for efficacy in this population. We had hoped that the adolescent period itself would allow generalisability of interventions. However, the variable reporting quality between studies, often without rich contextual descriptions, necessitate caution with interpretation of findings. This incomplete reporting also impacted on knowledge transfer at multiple levels, despite the use of study-specific guidelines. Our recommendations for future researchers would be to undertake adequately-powered studies among clearly defined age groups, and examine biological health outcomes for longer periods of follow-up. We also encourage researchers to use mHealth-specific guidelines such as the CONSORT-EHEALTH and mERA checklists to enable effective knowledge transfer and scaling of interventions.